Reduced miR-659-3p Levels Correlate with Progranulin Increase in Hypoxic Conditions: Implications for Frontotemporal Dementia - Piscopo, Paola; Grasso, Margherita; Fontana, Francesca; Crestini, Alessio; Puopolo, Maria; Del Vescovo, Valerio; Venerosi, Aldina; Calamandrei, Gemma; Vencken, Sebastian F.; Greene, Catherine M.; Confaloni, Annamaria; Denti, Michela A. (Frontiers in Molecular Neuroscience, 2016)
Progranulin (PGRN) is a secreted protein expressed ubiquitously throughout the body, including the brain, where it localizes in neurons and is activated microglia. Loss-of-function mutations in the GRN gene are an important cause of familial frontotemporal lobar degeneration (FTLD). PGRN has a neurotrophic and anti-inflammatory activity, and it is neuroprotective in several injury conditions, such as oxygen or glucose deprivation, oxidative injury, and hypoxic stress. Indeed, we have previously demonstrated that hypoxia induces the up-regulation of GRN transcripts. Several studies have shown microRNAs (miRNAs) involvement in hypoxia. Moreover, in FTLD patients with a genetic variant of GRN (rs5848), the reinforcement of miR-659-3p binding site has been suggested to be a risk factor. Here, we report that miR-659-3p interacts directly with GRN 3′UTR as shown by luciferase assay in HeLa cells and ELISA and Western Blot analysis in HeLa and Kelly cells. Moreover, we demonstrate the physical binding between GRN mRNA and miR-659-3p employing a miRNA capture-affinity technology in SK-N-BE and Kelly cells. In order to study miRNAs involvement in hypoxia-mediated up-regulation of GRN, we evaluated miR-659-3p levels in SK-N-BE cells after 24 h of hypoxic treatment, finding them inversely correlated to GRN transcripts. Furthermore, we analyzed an animal model of asphyxia, finding that GRN mRNA levels increased at post-natal day (pnd) 1 and pnd 4 in rat cortices subjected to asphyxia in comparison to control rats and miR-659-3p decreased at pnd 4 just when GRN reached the highest levels. Our results demonstrate the interaction between miR-659-3p and GRN transcript and the involvement of miR-659-3p in GRN up-regulation mediated by hypoxic/ischemic insults.